CULTURAL FEATURES OF FITZGERALD’S WORKS - Bekmurodova E’zoza (TADQIQOTLAR, 2025)
Annotation: This article explores the cultural features embedded in F. Scott Fitzgerald’s works, focusing on his portrayal of 20th-century American society, themes of the American Dream, and the cultural identity of the Jazz Age. Through an analysis of  key  texts,  including  The  Great  Gatsby,  the  study  highlights  Fitzgerald's  unique ability to reflect the societal values, challenges, and contradictions of his time.